2019
DOI: 10.1111/puar.13046
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Public–Private Partnerships in China: An Effective Financing Approach for Infrastructure Investment?

Abstract: The rise of public‐private partnerships (PPPs) in China has spurred heated debates about their purpose and effectiveness. This article traces the fluctuation of China's PPPs over several decades and finds that PPPs have played a supplementary role in China's infrastructure investment, as a response to the pressures of fiscal shortfalls and government debts. The resurgence of PPPs in recent years aims to bridge the infrastructure gap and alleviate ballooning local debts. These expectations, however, are hard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 20 publications
1
77
0
Order By: Relevance
“…Wang and Zhao [19] identified traffic demand, fiscal pressure, and PPP legislation as the main drivers of PPP adoption in highway tolling projects. Tan and Zhao [5] reviewed the development of PPP in China and indicated that PPP plays an important role in delivering infrastructure and reducing financial pressure.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and Zhao [19] identified traffic demand, fiscal pressure, and PPP legislation as the main drivers of PPP adoption in highway tolling projects. Tan and Zhao [5] reviewed the development of PPP in China and indicated that PPP plays an important role in delivering infrastructure and reducing financial pressure.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…This unprecedented increase within a short period naturally led to the question as to whether PPP had been over-adopted or even abused and whether it was helpful for the sustainable infrastructure development in urban China [5]. Although PPP, in general, is perceived to be more efficient than most traditional infrastructure procurement processes [6], literature points out that not all infrastructure projects are suitable for PPP [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We also present one Viewpoint article in this issue. In it, Tan and Zhao () question the rise of public–private partnerships in China and whether they can fulfill expectations to facilitate infrastructure development while reducing local debt burden.…”
mentioning
confidence: 99%
“…Moreover, GI development in cities always involves severe land-use conflict, as many GI projects are installed on non-public lands (Chini, Canning, Schreiber, Peschel, & Stillwell, 2017;Ryan, Fábos, & Allan, 2006). For this reason, the central government launched a Public-Private Partnership (PPP) policy in 2014 to encourage the private sector to engage and invest in the nation's sustainable city initiatives (Tan & Zhao, 2019).…”
Section: Author Contribution Statementmentioning
confidence: 99%
“…In the third-wave initiative, the central government attempted to establish 'real PPPs' by 'following the international PPP practice' to realize the benefits associated with PPPs (Lavanchy, 2018, p. 11). The Chinese government encouraged the public sector to collaborate with 'Enterprise Capitals', which includes both state-owned and private enterprises (Tan & Zhao, 2019). This research will examine the eco-environmental service partnerships in the third-wave initiative, which as initially established between the government and private non-SOEs were real PPPs.…”
Section: Introductionmentioning
confidence: 99%